The socioeconomic status of adult children, intergenerational support, and the well-being of Chinese older adults - Zhenhua Zheng; Ning Sun; Liu Yang; Wanting Liu; Yingchen Lu; Yusu Chu; Hong Chen (Humanities & Social Sciences Communications, 2023)
Abstract The well-being of older adults is significantly influenced by their adult children, especially in countries with less developed welfare systems. We aim to examine the relationship between children’s intergenerational support, children’s socioeconomic status and the well-being of older adults, as well as compare the differences among various elderly groups. The data in our research are from the 2014 China Longitudinal Aging Social Survey. The survey covered 29 provinces, autonomous regions and municipalities in China with 9146 valid samples. We adopted descriptive statistical analysis and structural equation modeling to analyze the data, and the bootstrap method to test the mediating effects. Our results indicate that the children’s education level and intergenerational support do not significantly affect the well-being of all groups of older adults in China. However, the financial conditions of adult children have a significant and direct impact on the well-being of all groups of older adults. From one child to multiple children, the impact of children’s financial condition on the well-being of older adults is 0.360, 0.452, 0.412 in three urban groups and 0.496, 0.468, 0.443 in three rural groups, specifically. The influence of adult children’s financial conditions on the well-being of all groups of older adults in China is significant, surpassing that of children’s education level and intergenerational support. Moreover, the impact of children’s socioeconomic status on the well-being of older adults is primarily through direct effects, with minimal intervention from intergenerational support. For older adults in China, "whether my children are living well" is more important than "what they could give me".